Sn / sb / in-based perovskite oxide catalyst and use thereof

CN116145179BActive Publication Date: 2026-10-23QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310081025.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2026-10-23
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

然而,由于复杂的电子/质子传递过程,以及CO2-HCOOH转化过程中催化剂活性结构的降解,使得Sn/Sb/In基催化剂仍存在法拉第效率低、稳定性差等挑战性问题

Benefits of technology

[0022]对于电催化二氧化碳还原制甲酸领域,虽然目前的一些研究在反应性能优化方面已取得一定效果,但其现阶段的研究仍然存在以下问题:CO2向HCOOH转化涉及复杂的电子-质子传递过程导致反应效率低;电催化反应过程中,催化剂活性结构降解,导致催化剂稳定性差。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116145179B_ABST
    Figure CN116145179B_ABST
Patent Text Reader

Abstract

The application belongs to the field of design and development of electrocatalytic carbon dioxide reduction catalysts, and particularly relates to a Sn / Sb / In-based perovskite oxide catalyst and application thereof in electrocatalytic carbon dioxide reduction to form formic acid. x A' y B m B' n O 3±δ Wherein, A and A' are perovskite A-site elements, and are respectively selected from one or more than one of Ln series metal elements and transition metal elements, B and B' are perovskite B-site elements, and are respectively selected from one or more than one of Sn, Sb and In elements, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of design and development of electrocatalytic carbon dioxide reduction catalysts, and in particular to a Sn / Sb / In-based perovskite oxide catalyst and its application in the electrocatalytic reduction of carbon dioxide to formic acid. Background Technology

[0002] The reduction of carbon dioxide using renewable electricity (i.e., carbon dioxide electroreduction, CER) into high-value-added chemical feedstocks and fuels is a promising technology for alleviating the current energy and environmental crisis. Among the various products of carbon dioxide reduction, formic acid (HCOOH) has attracted much attention due to its wide applications in pharmaceuticals, hydrogen transport, and fuel cells. However, the stable C=O covalent double bond of carbon dioxide, the high activation energy required for electrocatalysis, and the accompanying competitive hydrogen evolution reaction result in slow kinetics and low selectivity in the electrocatalytic reduction of carbon dioxide to formic acid, severely limiting its widespread application. Therefore, the development and design of high-performance CER catalysts are of great significance for the production of formic acid (HCOOH). Among them, tin (Sn) / antimony (Sb) / indium (In)-based catalysts stand out from various catalysts due to their unique adsorption properties for formic acid intermediates. Sn / Sb / In-based catalysts have weak adsorption energies for CO and H, but strong adsorption energies for the OCH2O intermediate, and can generate large amounts of formic acid by stabilizing the OCH2O intermediate and subsequent hydrogenation. However, due to the complex electron / proton transfer process and the degradation of the catalyst's active structure during the CO2-HCOOH conversion, Sn / Sb / In-based catalysts still face challenges such as low Faraday efficiency and poor stability. Therefore, further research is needed to explore advanced HCOOH catalysts to achieve stable and efficient HCOOH production. Summary of the Invention

[0003] The purpose of this invention is to improve upon the shortcomings of existing CER technology for producing HCOOH by providing a Sn / Sb / In-based perovskite oxide and its application in the electrocatalytic reduction of carbon dioxide to formic acid.

[0004] To achieve the above objectives, the present invention adopts the following technical solution:

[0005] A Sn / Sb / In-based perovskite oxide catalyst, wherein the general formula of Sn / Sb / In-based perovskite oxide is A x A′ y B m B′ n O 3±δ, wherein A and A' are perovskite A-site elements, each independently selected from one or more of lanthanide series metal elements and transition metal elements; B and B' are perovskite B-site elements, each independently selected from one or more of Sn, Sb and In elements, 0<x≤1, 0<y≤1, 0<m≤1, 0<n≤1, (x+y≤1, m+n≤1), δ represents oxygen deficiency, and its value is related to the valence difference between the cations at A and B sites and oxygen.

[0006] Said A and A' are each independently selected from one or more of La, Pr, Nd, Sm, Eu, Gd, Sr, Ba and Ca.

[0007] A preparation method of the aforementioned perovskite oxide catalyst:

[0008] A. Salts containing the raw material elements are weighed according to the stoichiometric ratio of the material, mixed with ethanol, and then ground in a high-energy ball mill for later use after mixing.

[0009] B. The ball-milled raw material is dried, placed in a muffle furnace for high-temperature calcination, cooled to room temperature and then taken out to obtain a perovskite oxide precursor.

[0010] C. The perovskite oxide precursor is calcined again at high temperature in a muffle furnace to obtain the perovskite oxide with the general formula A x A' y B m B' n O 3±δ perovskite oxide;

[0011] D. The perovskite oxide with the aforementioned general formula A x A' y B m B' n O 3±δ is subjected to ball milling treatment again to obtain a perovskite oxide with a smaller particle size.

[0012] F. The aforementioned perovskite oxide is mixed with ethanol and Nafion, and ultrasonicated to be uniform to obtain a liquid-phase catalyst.

[0013] In step A, the ball milling time is 1-8 h, and the rotation speed is 500-750 rpm.

[0014] In step B, the heating rate for calcination is 1-5°C / min, the temperature is 900-1100°C, the calcination time is 5-10 h, and the cooling rate is 2-5°C / min; in step C, the heating rate for calcination is 1-5°C / min, the temperature is 1100-1300°C, the calcination time is 1-4 h, and the cooling rate is 2-5°C / min.

[0015] In step D, the ball milling time is 1-8 hours, the rotation speed is 500-750 rpm, and the particle size of the perovskite oxide after ball milling is 50-300 nm.

[0016] In step F, the mixing ratio of perovskite oxide with ethanol and Nafion is 1 mg: 90-100 μl: 5 μl, and the ultrasonic time is 30-120 min.

[0017] An application of the perovskite oxide catalyst, wherein the perovskite oxide is used as an electrocatalytic carbon dioxide reduction catalyst in the production of formic acid.

[0018] A method for electrocatalytic reduction of carbon dioxide to formic acid, wherein the perovskite oxide is used as a catalyst for electrocatalytic reduction of carbon dioxide to formic acid.

[0019] This invention relates to the principle:

[0020] The Sn / Sb / In-based perovskite oxide of this invention has the molecular formula A. x A′ y B m B′ n O 3±δ The A-site cation has a 12-coordinate structure, located at the 12 vertices of the cubic unit cell; the B-site cation coordinates with 6 oxygen ions, forming a BO6 octahedral structure. Introducing multiple elements at the A and B sites offers advantages over traditional ABO3 perovskites, including a richer composition, a more complex atomic environment, and better chemical stability, potentially leading to superior electrocatalytic performance. Typically, the B-site cation and / or BO bond directly affect the electrocatalytic performance of perovskite oxide catalysts. This invention introduces Sn / Sb / In elements into the perovskite B-site as the catalytic active center, achieving excellent CER to HCOOH production performance. Furthermore, the catalytic performance of perovskite oxides can be further optimized through A-site / O-site regulation: ① The A-site cation indirectly affects the catalytic performance of perovskite by influencing the electronic structure of the B-site / BO bond. Therefore, the electronic structure of the B-site / BO bond can be regulated by introducing multiple elements at the A-site, and the activity and stability of the catalyst can be further improved through electronic interactions and electron density rearrangement; ② If there is a valence state difference between the A-site cation and the oxygen ion, oxygen vacancies and other oxygen defects may be formed. Oxygen defects are conducive to the generation of new electron-hole pairs, improve charge transfer, and also change the surface and interface structure of the catalyst, enhance the adsorption and dissociation of key intermediates, thereby improving the activity of the catalyst.

[0021] Beneficial effects:

[0022] In the field of electrocatalytic carbon dioxide reduction to formic acid, although some studies have achieved certain results in optimizing reaction performance, the current research still has the following problems: the conversion of CO2 to HCOOH involves a complex electron-proton transfer process, resulting in low reaction efficiency; during the electrocatalytic reaction, the active structure of the catalyst degrades, resulting in poor catalyst stability.

[0023] In this invention, readily available and easily prepared Sn / Sb / In-based perovskite oxides are used as catalysts for the CER production of formic acid. This is primarily due to the excellent properties of perovskite oxides themselves (rich chemical composition, flexible and diverse structures, and tunable physicochemical properties), which exhibit good catalytic activity. Secondly, the introduction of multiple elements into the A and B sites of the perovskite further enriches its composition, making its atomic environment more complex and stable. Thirdly, the B-site cation / BO bond directly affects the electrocatalytic activity of the perovskite oxide; by introducing Sn / Sb / In elements (with good HCOOH activity and selectivity) into the B-site, a Sn / Sb / In-based catalyst is constructed. Perovskite oxide catalysts are beneficial for achieving excellent CER (concentrated oxidative stress) performance in the production of formic acid. Simultaneously, the properties of the A-site cation in perovskite oxides influence the coordination environment of the B-site cation (BO bond length, covalentity, etc.). Therefore, by controlling the A-site elements, the size and electronegativity of the A-site cation can be effectively controlled, thereby altering the physicochemical properties of the B-site active site and promoting the catalyst's activity, selectivity, and stability. Finally, creating oxygen vacancies can also effectively regulate the electronic structure of perovskite, improve charge transfer capabilities, alter the surface crystal structure, enhance the dissociation and adsorption of key intermediates, and thus regulate the catalytic performance of perovskite oxide catalysts. Attached Figure Description

[0024] Figure 1 Ba prepared in Example 1 0.5 Sr 0.5 Microscopic morphology of SnO3 surface

[0025] Figure 2 Ba prepared in Example 1 0.5 Sr 0.5 CER product distribution and FE efficiency plot of SnO3;

[0026] Figure 3 Ba prepared in Example 1 0.5 Sr 0.5 Stability test results of SnO3 catalyst for electrocatalytic carbon dioxide reduction;

[0027] Figure 4 Ba prepared in Example 1 0.5 Sr 0.5 XRD patterns of SnO3 catalyst before and after CER reaction;

[0028] Figure 5 Ba prepared for implementation of Case 1 0.5 Sr 0.5 Comparison of SnO3 performance with perovskite catalysts of different Ba / Sr ratios. Detailed Implementation

[0029] The following examples further illustrate specific embodiments of the present invention. It should be noted that the specific embodiments described herein are merely for illustration and explanation and are not intended to limit the scope of the present invention.

[0030] The Sn / Sb / In-based perovskite oxide material of this invention exhibits excellent performance in the electrocatalytic reduction of CO2 to CHOOH, effectively solving the problems of low Faradaic efficiency and poor stability of CO2 to CHOOH catalysts. Furthermore, the catalyst performance can be further improved through simple and universal perovskite material regulation methods such as A-site cation regulation, B-site cation regulation, and oxygen defect regulation. This results in a catalyst with good selectivity and high Faradaic efficiency for formic acid in the electrocatalytic reduction of CO2, and it maintains excellent stability and reactivity even after long-term testing. It is suitable for long-term operation of electrocatalytic reduction of CO2 to formic acid (HCOOH), meeting the needs of industrial applications.

[0031] Example 1

[0032] Ba, the material of this invention, was prepared by high-temperature solid-state synthesis. 0.5 Sr 0.5 Taking the electrocatalytic reduction of carbon dioxide with SnO3 as an example:

[0033] Commercially available BaCO3, SrCO3, and SnO2 were mixed with ethanol in stoichiometric ratio and ball-milled at high energy for 1 hour to ensure homogeneity. The sample was dried and then calcined in a muffle furnace at 1000℃ for 10 hours. The calcined sample was then further calcined at 1200℃ for 2 hours. The heating and cooling rates were both 5℃ / min. After cooling to room temperature, the sample was ball-milled at 600 rpm for 1 hour to obtain BaCO3. 0.5 Sr 0.5 SnO3 catalyst powder sample (see) Figure 1 ).

[0034] The surface microstructure of the catalyst is as follows Figure 1 As can be seen from the figure, Ba 0.5 Sr 0.5 The powder size of SnO3 catalyst is around 200-300 nm.

[0035] Performance determination of the catalysts obtained above:

[0036] 1) Electrocatalytic performance test:

[0037] Will Ba0.5 Sr 0.5 SnO3 powder was mixed with an ethanol / Nafion mixed solution to prepare a catalyst dispersion, which was then used for electrocatalytic carbon dioxide reduction testing. Specifically:

[0038] A. will Ba 0.5 Sr 0.5 SnO3 powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion, and then sonicated for 30 min to mix evenly.

[0039] B. Drop the uniformly dispersed liquid catalyst onto hydrophobic carbon paper and dry it.

[0040] C. The carbon paper coated with the catalyst is placed into a flowing electrolytic cell. A three-electrode system is used, with a Pt electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and the catalyst supported on the carbon paper as the working electrode. A 1 mol / L KOH solution is used as the electrolyte solution and is circulated to the cathode chamber of the electrolytic cell via a peristaltic pump.

[0041] D. CO2 is introduced into the gas diffusion layer of the flowing electrolytic cell. After energization, the CO2 electrocatalytic reduction reaction takes place on the catalyst surface and at the three-phase interface between the catalyst, CO2, and electrolyte solution.

[0042] Depend on Figure 2 It can be seen that the Ba 0.5 Sr 0.5 SnO3 catalysts exhibit excellent CO2 electrocatalytic conversion capabilities, with formic acid Faraday efficiencies exceeding 90% at various potentials (-1.4 to -2.4 V vs. RHE).

[0043] 2) Catalyst stability testing:

[0044] The catalyst prepared above was subjected to stability testing at -1.0V (vs. RHE) (see [reference]). Figure 3 ).

[0045] from Figure 3 It can be seen that the catalyst can be stabilized for 15 hours at -1.0V (vs. RHE).

[0046] 3) Catalyst characterization:

[0047] The catalyst after the above 15-hour stability test was characterized by X-ray diffraction (see [reference]). Figure 4 ).

[0048] from Figure 4As can be seen, the X-ray diffraction pattern after the stability test still shows a distinct perovskite phase. Compared with the X-ray diffraction pattern before the reaction, there is no significant change, proving that the catalyst has not undergone significant changes, maintains the integrity of the active catalytic structure, and has not degraded, making it suitable for industrial applications in the field of electrocatalytic carbon dioxide reduction.

[0049] 4) Modulate the catalyst to further improve the selectivity of formic acid.

[0050] The catalyst prepared above was subjected to A-site cation regulation, i.e., the Ba / Sr ratio was changed, and its catalytic performance was tested. (See...) Figure 5 )

[0051] from Figure 5 It can be seen that as the ratio of Ba / Sr cations at the A site changes, i.e., the A site is controlled, the selectivity of the perovskite catalyst for CHOOH shows a clear pattern. There is an optimal Ba / Sr ratio that gives the perovskite oxide the best catalytic performance.

[0052] Example 2

[0053] Ba, the material of this invention, was prepared by high-temperature solid-state synthesis. 0.25 Sr 0.75 Sn 0.9 Sb 0.1 Taking the electrocatalytic reduction of carbon dioxide with O3 as an example

[0054] Commercially available BaCO3, SrCO3, SnO2, and Sb2O5 were mixed with ethanol according to their stoichiometric ratios and ball-milled at high energy for 1 hour to ensure homogeneity. The sample was dried and then calcined in a muffle furnace at 1000℃ for 10 hours. The calcined sample was then further calcined at 1200℃ for 4 hours. The heating and cooling rates were both 2℃ / min. The cooled sample was then ball-milled at 600 rpm for 3 hours to obtain Ba2O3. 0.25 Sr 0.75 Sn 0.9 Sb 0.1 O3 catalyst powder sample.

[0055] The surface micrograph of the catalyst shows that the powder diameter is about 150 nm.

[0056] Then, following the electrocatalytic performance test procedure described in Example 1 above, Ba... 0.25 Sr 0.75 Sn 0.9 Sb 0.1O3 powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 95% at -1.0 V (vs. RHE) formic acid.

[0057] The catalyst was also subjected to stability testing at -1.0V (vs. RHE), and remained stable for 30 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pattern before the reaction. This demonstrates that the catalyst has not undergone significant alteration and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0058] Example 3

[0059] Ba, the material of this invention, was prepared by high-temperature solid-state synthesis. 0.75 Sr 0.25 Sb 0.5 In 0.5 Taking the electrocatalytic reduction of carbon dioxide with O3 as an example

[0060] Commercially available BaCO3, SrCO3, SnO2, Sb2O5, and In2O3 were mixed with ethanol according to their stoichiometric ratios and ball-milled at high energy for 1 hour to ensure homogeneity. The sample was dried and calcined in a muffle furnace at 900℃ for 8 hours. The calcined sample was then further calcined at 1100℃ for 2 hours. The heating and cooling rates were both 2℃ / min. The cooled sample was then ball-milled at 600 rpm for 1 hour to obtain Ba... 0.75 Sr 0.25 Sb 0.5 In 0.5 O3 catalyst powder sample.

[0061] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 200 nm.

[0062] Will Ba 0.75 Sr 0.25 Sb 0.5 In 0.5 O3 powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 96% at -1.0 V (vs. RHE) formic acid.

[0063] The catalyst was stabilized at -1.0V (vs. RHE) for 30 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the X-ray diffraction pattern before the reaction. This demonstrates that the catalyst has not undergone significant alteration and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0064] Example 4

[0065] The La material of this invention was prepared by high-temperature solid-state synthesis. 0.2 Ba 0.6 Taking the electrocatalytic reduction of carbon dioxide using SbO3 as an example, commercially available La2O3, BaCO3, and Sb2O5 were mixed with ethanol according to the stoichiometric ratio of the materials, and then ball-milled at high energy for 1 hour to ensure uniform mixing. After drying, the sample was calcined in a muffle furnace at 1100℃ for 10 hours. The calcined sample was then calcined again at 1200℃ for 4 hours. The heating and cooling rates were both 2℃ / min. The cooled sample was then ball-milled at 600 rpm for 2 hours to obtain La2O3. 0.2 Ba 0.6 SbO3 catalyst powder sample.

[0066] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 200 nm.

[0067] La 0.2 Ba 0.6 SbO3 powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 96% at -1.0 V (vs. RHE) formic acid.

[0068] The catalyst was stabilized at -1.0V (vs. RHE) for 40 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0069] Example 5

[0070] The La material of this invention was prepared by high-temperature solid-state synthesis. 0.2 Ba 0.7 In 0.4 Sb 0.4 Sn 0.2 O 3-δTaking electrocatalytic carbon dioxide reduction as an example, commercially available La₂O₃, BaCO₃, Sb₂O₅, In₂O₃, and SnO₂ were mixed with ethanol according to their stoichiometric ratios and ball-milled at high energy for 1 hour to ensure homogeneity. After drying, the sample was calcined in a muffle furnace at 1000℃ for 10 hours. The calcined sample was then calcined again at 1200℃ for 2 hours. The heating and cooling rates were both 5℃ / min. The cooled sample was then ball-milled at high energy for 1 hour to obtain La₂O₃. 0.2 Ba 0.7 In 0.4 Sb 0.4 Sn 0.2 O 3-δ Catalyst powder sample.

[0071] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 200 nm.

[0072] La 0.2 Ba 0.7 In 0.4 Sb 0.4 Sn 0.2 O 3-δ The powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 90% at -1.0 V (vs. RHE) formic acid.

[0073] The catalyst was stabilized at -1.0V (vs. RHE) for 20 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0074] Example 6

[0075] The La material of this invention was prepared by high-temperature solid-state synthesis. 0.2 Sr 0.2 Ca 0.2 Ba 0.2 Sn 0.8 In 0.2 O 3+δTaking electrocatalytic carbon dioxide reduction as an example, commercially available La₂O₃, SrCO₃, CaCO₃, BaCO₃, SnO₂, and In₂O₃ were mixed with ethanol according to the stoichiometric ratio of the materials, and ball-milled at high energy for 1 hour to ensure uniform mixing. After drying, the sample was calcined in a muffle furnace at 900℃ for 10 hours. The calcined sample was then calcined again at 1200℃ for 3 hours. The heating and cooling rates were both 3℃ / min. The cooled sample was ball-milled at 500 rpm for 3 hours to obtain La₂O₃. 0.2 Sr 0.2 Ca 0.2 Ba 0.2 Sn 0.8 In 0.2 O 3+δ Catalyst powder sample.

[0076] The surface micrograph of the catalyst shows that the powder diameter is about 150 nm.

[0077] La 0.2 Sr 0.2 Ca 0.2 Ba 0.2 Sn 0.8 In 0.2 O 3+δ The powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 95% at -1.0 V (vs. RHE) formic acid.

[0078] The catalyst was stabilized at -1.0V (vs. RHE) for 40 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0079] Example 7

[0080] The La material of this invention was prepared by high-temperature solid-state synthesis. 0.5 Pr 0.5 Taking InO3 as an example of electrocatalytic carbon dioxide reduction, commercially available La2O3 and Pr6O3 are used in stoichiometric ratios according to the materials. 11In₂O₃ was mixed with ethanol at a stoichiometric ratio and ball-milled at high energy for 1 hour to ensure homogeneity. The sample was dried and then calcined in a muffle furnace at 1000℃ for 5 hours. The calcined sample was then further calcined at 1200℃ for 4 hours. The heating and cooling rates were both 2℃ / min. The cooled sample was then ball-milled at 500 rpm for 1 hour to obtain La. 0.5 Pr 0.5 InO3 catalyst powder sample.

[0081] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 250 nm.

[0082] La 0.5 Pr 0.5 InO3 powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 96% at -1.0 V (vs. RHE) formic acid.

[0083] The catalyst was stabilized at -1.0V (vs. RHE) for 20 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0084] Example 8

[0085] The La material of this invention was prepared by high-temperature solid-state synthesis. 0.2 Pr 0.2 Nd 0.6 Taking InO3 as an example of electrocatalytic carbon dioxide reduction, commercially available La2O3 and Pr6O3 are used in stoichiometric ratios according to the materials. 11 Nd₂O₃ and In₂O₃ were mixed with ethanol in stoichiometric ratio and ball-milled at high energy for 1 hour to ensure homogeneity. The sample was dried and then calcined in a muffle furnace at 1000℃ for 5 hours. The calcined sample was then further calcined at 1200℃ for 4 hours. The heating and cooling rates were both 2℃ / min. The cooled sample was then ball-milled at high energy for 1 hour to obtain La. 0.2 Pr 0.2 Nd 0.6 InO3 catalyst powder sample.

[0086] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 250 nm.

[0087] La 0.2 Pr0.2 Nd 0.6 InO3 powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested, and the perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 95% at -1.0 V (vs. RHE) formic acid.

[0088] The catalyst was stabilized at -1.0V (vs. RHE) for 25 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0089] Example 9

[0090] The Nd material of this invention was prepared by high-temperature solid-state synthesis. 0.5 Sm 0.5 In 0.9 Sb 0.1 Taking the electrocatalytic reduction of carbon dioxide using O3 as an example, commercially available Nd2O3, Sm2O3, In2O3, and Sb2O5 were mixed with ethanol according to the stoichiometric ratio of the materials, and then ball-milled at high energy for 1 hour to ensure uniform mixing. After drying, the sample was calcined in a muffle furnace at 1100℃ for 10 hours. The calcined sample was then calcined again at 1200℃ for 4 hours. The heating and cooling rates were both 3℃ / min. The cooled sample was then ball-milled at high energy for 3 hours to obtain Nd2O3. 0.5 Sm 0.5 In 0.9 Sb 0.1 O3 catalyst powder sample.

[0091] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 180 nm.

[0092] Nd 0.5 Sm 0.5 In 0.9 Sb 0.1 O3 powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 95% at -1.0 V (vs. RHE) formic acid.

[0093] The catalyst was stabilized at -1.0V (vs. RHE) for 25 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0094] Example 10

[0095] The La material of this invention was prepared by high-temperature solid-state synthesis. 0.2 Pr 0.2 Nd 0.2 Sm 0.4 In 0.4 Sb 0.4 Sn 0.2 O 3-δ Taking electrocatalytic carbon dioxide reduction as an example, commercially available La2O3 and Pr6O3 are used in stoichiometric proportions according to the stoichiometric ratio of the materials. 11 Nd₂O₃, Sm₂O₃, In₂O₃, Sb₂O₅, and SnO₂ were mixed with ethanol in stoichiometric ratio and ball-milled at high energy for 1 hour to ensure homogeneity. The sample was dried and then calcined in a muffle furnace at 1000℃ for 10 hours. The calcined sample was then further calcined at 1200℃ for 2 hours. The heating and cooling rates were both 5℃ / min. The cooled sample was then ball-milled at high energy for 1 hour to obtain La. 0.2 Pr 0.2 Nd 0.2 Sm 0.4 In 0.4 Sb 0.4 Sn 0.2 O 3-δ Catalyst powder sample.

[0096] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 200 nm.

[0097] La 0.2 Pr 0.2 Nd 0.2 Sm 0.4 In 0.4 Sb 0.4 Sn 0.2 O 3-δ The powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 95% at -1.0 V (vs. RHE) formic acid.

[0098] The catalyst was stabilized at -1.0V (vs. RHE) for 25 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0099] Example 11

[0100] Ba, the material of this invention, was prepared by high-temperature solid-state synthesis. 0.2 Sr 0.2 Pr 0.3 Nd 0.3 InO 3-δ Taking electrocatalytic carbon dioxide reduction as an example, commercially available BaCO3, SrCO3, and Pr6O are used in stoichiometric proportions according to the materials. 11 Nd₂O₃ and In₂O₃ were mixed with ethanol in stoichiometric ratio and ball-milled at high energy for 1 hour to ensure homogeneity. The sample was dried and then calcined in a muffle furnace at 1000℃ for 10 hours. The calcined sample was then further calcined at 1200℃ for 2 hours. The heating and cooling rates were both 5℃ / min. The cooled sample was ball-milled at high energy for 1 hour to obtain Ba. 0.2 Sr 0.2 Pr 0.3 Nd 0.3 InO 3-δ Catalyst powder sample.

[0101] The surface micrograph of the catalyst shows that the diameter of the catalyst powder is about 200 nm.

[0102] Will Ba 0.2 Sr 0.2 Pr 0.3 Nd 0.3 InO 3-δ The powder was mixed with ethanol and Nafion solution at a ratio of 1 mg: 100 μl: 5 μl to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The perovskite catalyst material showed good electrocatalytic carbon dioxide reduction performance, with a Faradaic efficiency of over 95% at -1.0 V (vs. RHE) formic acid.

[0103] The catalyst was stabilized at -1.0V (vs. RHE) for 25 hours. The X-ray diffraction pattern after the stability test still showed a distinct perovskite phase, with no significant change compared to the pre-reaction X-ray diffraction pattern, indicating that the catalyst remained largely unchanged and is suitable for industrial applications in electrocatalytic carbon dioxide reduction.

[0104] Compare with Example 1

[0105] Taking commercial tin dioxide (SnO2) for electrocatalytic carbon dioxide reduction as an example, a certain amount of tin dioxide (SnO2) was ball-milled using a high-energy ball mill at 600 rpm for 1 hour. The surface microstructure of the catalyst showed that the powder diameter of the catalyst was about 50 nm.

[0106] The catalyst was mixed with a certain proportion of ethanol and Nafion solution to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The performance of commercial tin dioxide (SnO2) in carbon dioxide reduction was generally poor, with a Faraday efficiency of 86% at -1.0V (vs. RHE) formic acid.

[0107] The catalyst was tested for stability at -1.0V (vs. RHE), and it remained stable for only about 1 hour at this temperature. Compared to tin-based perovskite oxide catalysts, commercial tin dioxide (SnO2) exhibits poorer performance and moderate stability in carbon dioxide reduction.

[0108] Compare with Example 2

[0109] Taking commercial indium trioxide (In2O3) for electrocatalytic carbon dioxide reduction as an example, a certain amount of indium trioxide (In2O3) was ball-milled using a high-energy ball mill at 600 rpm for 1 hour. The surface microstructure of the catalyst showed that the powder diameter of the catalyst was about 50 nm.

[0110] The catalyst was mixed with a certain proportion of ethanol and Nafion solution to prepare a catalyst dispersion. Electrocatalytic carbon dioxide reduction was then tested. The performance of indium trioxide (In2O3) in carbon dioxide reduction was generally poor, with a Faraday efficiency of 80% at -1.0V (vs. RHE) formic acid.

[0111] The catalyst was tested for stability at -1.0V (vs. RHE), and it remained stable for less than 5 hours at this temperature. Compared to indium-based perovskite oxide catalysts, indium trioxide (In₂O₃) exhibits poorer carbon dioxide reduction performance and moderate stability.

Claims

1. An application of a Sn / Sb / In-based perovskite oxide catalyst, characterized in that: Application of Sn / Sb / In-based perovskite oxide as an electrocatalytic carbon dioxide reduction catalyst in formic acid production; the general formula of the Sn / Sb / In-based perovskite oxide is A x A' y B m B' n O 3±δ , wherein A is selected from one or more of La, Pr, Nd, Sm, Eu and Gd, A' is selected from one or more of Sr, Ba and Ca, B and B' are each independently selected from one or more of Sn, Sb and In elements, 0<x≤1, 0<y≤1, 0<m≤1, 0<n≤1, x+y≤1, m+n≤1, and δ represents oxygen vacancy.

2. The application according to claim 1, characterized in that: The preparation method of the Sn / Sb / In-based perovskite oxide is as follows: A. Weigh the salt containing the raw material elements according to the stoichiometric ratio of the perovskite oxide, mix with ethanol, and then ball mill using a high-energy ball mill for later use; B. Dry the ball-milled raw material, place it in a muffle furnace for high-temperature calcination, cool it to room temperature and remove it to obtain the perovskite oxide precursor. C. The perovskite oxide precursor is calcined again at high temperature in a muffle furnace to obtain the general formula A. x A′ y B m B′ n O 3±δ Perovskite oxides; D. The general formula is A x A′ y B m B′ n O 3±δ The perovskite oxide was ball-milled again to obtain perovskite oxide with a particle size of 50-300 nm. E. The above perovskite oxide is mixed with ethanol and Nafion, and then ultrasonicated to obtain a catalyst dispersion.

3. The application according to claim 2, characterized in that: In step A, the ball milling time is 1-8 hours and the rotation speed is 500-750 rpm.

4. The application according to claim 2, characterized in that: In step B, the calcination heating rate is 1-5 ℃ / min, the temperature is 900-1100 ℃, the calcination time is 5-10 h, and the cooling rate is 2-5 ℃ / min; in step C, the calcination heating rate is 1-5 ℃ / min, the temperature is 1100-1300 ℃, the calcination time is 1-4 h, and the cooling rate is 2-5 ℃ / min.

5. The application according to claim 2, characterized in that: In step D, the ball milling time is 1-8 hours and the rotation speed is 500-750 rpm.

6. The application according to claim 2, characterized in that: In step E, the mixing ratio of perovskite oxide with ethanol and Nafion is 1 mg: 90-100 μl: 5 μl, and the sonication time is 30-120 min.

Citation Information

Patent Citations

  • Preparation and application of indium-based perovskite catalyst LaInO3

    CN114990612A

  • METHOD OF PRODUCING INDATES OF RARE-EARTH ELEMENTS InO3

    RU2688606C1